INVESTIGATION ON DELIGNIFICATION AND PULPING OF SPRUCE (PICEA ABIES) - Abbas Fakhryan roghani (Regional Information Center for Science and Technology (RICeST), 2003)
Two 22 years old spruce trees (Picea abies) from Picesoon region of Gilan province are investigated. These samples were transferred to the Alborz research center. The physical, anatomical and chemical properties of samples were determined. Dry and critical specific gravity, fiber length, amount of cellulose and lignin were measured at 0.334, 0.306, 3.07 mm, % 59.74 and % 28.94 respectively. Average yield and kappa number of kraft pulp at %16, %18 and % 20 effective alkalis were determined at 48/67%, 44.67%, 45.63% and 46.85, 33.98 and 26.89 respectively. The result of this research indicates that production of suitable pulp from picea abies wood is possible.